Adverse events of the thyroid peroxidase inhibitor methimazole in the treatment of hyperthyroidism: a comprehensive analysis from the first quarter of 2004 to the first quarter of 2025 - Sun, Yixin; Wang, Shuai; Zhou, Xu (Frontiers in Endocrinology, 2025)
PurposeThe primary objective of this study is to systematically monitor and comprehensively characterize adverse events (AEs) associated with methimazole, which is utilized in the treatment of hyperthyroidism.MethodA comprehensive analysis of the US FDA Adverse Event Reporting System (FAERS) database was conducted, covering data from the first quarter of 2004 to the first quarter of 2025. Multiple signal detection algorithms, including the ROR, PRR, BCPNN, and EBGM, were employed for conduct disproportionality analysis to efficiently mine the data and accurately identify signals associated with AEs related to methimazole.ResultAfter analyzing 1,908 patient cases with 6,449 reported AEs linked to methimazole, the study confirmed AEs like agranulocytosis, pyrexia, hypothyroidism, and drug-induced liver injury aligning with the drug’s package insert. Interestingly, several previously unreported AEs, such as premature baby, polyarthritis, pleural effusion, septic shock, cholestasis and jaundice cholestatic were identified. The findings indicate potential unrecognized AEs and highlight the importance of continued pharmacovigilance and rigorous drug safety surveillance. The median onset time of methimazole related AEs was 27 days (interquartile range [IQR]: 5–58 days), indicating that the majority of cases occurred early after initiating use methimazole.ConclusionThis study confirms that agranulocytosis, pyrexia, exposure during pregnancy, and hyperthyroidism are AEs associated with methimazole use. It also identifies new safety signals, including premature infants, polyarthritis, pleural effusion, septic shock, cholestasis, and cholestatic jaundice, that warrant further investigation. These findings support deeper analysis of the relationship between methimazole and adverse events and may help improve patient safety and clinical outcomes.